Analisis Pemasaran Tandan Buah Segar Kelapa Sawit Kecamatan Putri Hijau, Kabupaten Bengkulu Utara - Sumartono, Eko; Suryanty, Melly; Badruddin, Redy; Rohman, Agus (Universitas Muhammadiyah Yogyakarta, 2018)
The sale of fresh fruit bunches in Putri Hijau sub-district has variety of marketing channels from farmers to consumers. The diversity of marketing channels should result in differences in the price levels received by farmers and the costs incurred by each marketing agency, such as freight costs, transportation costs to factories, fruit shrinkage costs, and other costs. This study aims to identify marketing channels and compare the marketing channel efficiency of fresh fruit bunches (TBS) of palm oil formed in Kecamatan Putri Hijau, North Bengkulu. Determination of farmer respondents is done by purposive sampling counted 41 people, and marketing agency respondents use snowball sampling method. The results showed that there are three channels of marketing of oil palm FFS formed, namely Channel I (farmers - collector traders - factories), Channel II (farmers - farmer groups - factories), Channel III (farmers - factories). The most widely used channels by farmers are channel I (farmers - collectors – mills) that have the highest margin and low farmer’s share. The merchandise margin and the profit-to-cost ratio indicate that only marketing channel I in Bani Village is efficient. Marketing channel I in Desa Bani Village has a marketing margin value of Rp206/kg with the value of profit to marketing cost ratio of 1.17.